The Effect of Painting-Based Art Therapy on Aggressive Behavior of Female Students with Hearing Impairment - Rahimi pordanjani , Saeed; Jalali , Darioush; Nejatifar, Sara; Arabi , Elaheh (Journal of Assessment and Research in Applied Counseling (JARAC), 2021)
Background and Aim: Adaptation problems in children with hearing impairment require therapeutic interventions. Therefore, this study was conducted to investigate the effect of painting-based art therapy on the aggressive behavior of female students with hearing impairment. Methods: This was a quasi-experimental study with a pretest-posttest design, control and experimental groups, and a three-month follow-up. The statistical population included female students with hearing impairment who were studying in special schools of Shahrekord in the academic year 2019-2020, from which 30 students who met the inclusion criteria were selected by the convenient sampling method and assigned to the experimental group (n = 15) and the control group (n = 15) after matching. The experimental group received a painting therapy package for 15 sessions, and the control group received no intervention. All subjects were assessed in the pre-test and post-test stages by Buss and Perry’s (1992) Aggression Questionnaire. Data were analyzed using repeated-measures ANOVA and SPSS 24 software. Results: The results indicated that painting-based art therapy reduced aggressive behavior and the components of anger, verbal aggression, and resentment both in the post-test and follow-up stages (P<0.01). Conclusion: According to the results, painting-based art therapy is recommended to therapists in the field of children with special needs as an effective psychotherapy method to reduce the clinical signs of aggressive behavior disorder in students.